2013
DOI: 10.1162/rest_a_00222
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being over the Life Span: Semiparametric Evidence from British and German Longitudinal Data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 64 publications
3
66
0
2
Order By: Relevance
“…Wunder et al (2009) hence include a fourth-order polynomial of age in their happiness regressions, where they find that the higher order terms are also significant and hence that the U-shape is not a perfect description of the actual relationships (they find a clear negative slope at the very high age ranges). We will in this paper also look at the full age-profile later on, but initially will follow the literature and focus on a second-order polynomial (age and age-squared).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Wunder et al (2009) hence include a fourth-order polynomial of age in their happiness regressions, where they find that the higher order terms are also significant and hence that the U-shape is not a perfect description of the actual relationships (they find a clear negative slope at the very high age ranges). We will in this paper also look at the full age-profile later on, but initially will follow the literature and focus on a second-order polynomial (age and age-squared).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The GSOEP currently tracks about 20,000 individuals and 12,000 households. See Wunder et al (2009) for a detailed description of the data and summary statistics.…”
Section: The Gsoepmentioning
confidence: 99%
“…Based on a European sample, it was estimated that the minimum happiness occurred between 45 and 50 years of age for both males and females (Blanchflower & Oswald, 2008). However, other investigators have found that the happiness curve illustrated a range of forms including flat development, an inverted U-shape, or an approximation of a U-shape, until the late 60s followed by a decline in happiness (Easterlin, 2006; Frijters & Beatton, 2012; Gerstorf et al, 2010; Wunder, Wiencierz, Schwarze, & Kuchenhoff, 2013). In comparison, age-related differences in domains such as physical and mental functions very consistently take the form of a deteriorating curve which may well deteriorate at different speeds and even accelerate in the oldest old, but not forming a U-shaped curve (Andersen-Ranberg et al, 1999; Crimmins & Beltran-Sanchez, 2011; Frederiksen et al, 2006; McGue & Christensen, 2013; Stathokostas, Jacob-Johnson, Petrella, & Paterson, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…For example, an increasing body of studies suggests a U-shaped relationship between age and SwL over the life cycle. Based on the suggested Ushaped or curvilinear pattern, life satisfaction decreases to midlife, and then subsequently increases towards retirement (19)(20)(21). The main reason for this could be positive psychological states at younger and older ages.…”
Section: Discussionmentioning
confidence: 99%